2010
DOI: 10.1002/elsc.200900080
|View full text |Cite
|
Sign up to set email alerts
|

Chemometric methods for simultaneous quantification of lactic, malic and fumaric acids

Abstract: Lactic, fumaric and malic acids are commonly used in food and pharmaceutical industries. During microbial production of these compounds, it is important to determine their concentrations in the fermentation broth with a rapid and sensitive method. Spectrophotometry is commonly used. However, UV‐spectral overlap between these organic acids makes it difficult to determine each of them individually from the mixture. In order to overcome this problem, statistical methods, namely principal component regression (PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…In this study, the total organic acids was measured directly in clear supernatant after centrifugation and filtration using spectrophotometer at 220 nm (Sokullu et al, 2010) and values were compared to uninoculated control samples. Specific organic acids were not determined at this stage of this study.…”
Section: Determination Of Total Organic Acidsmentioning
confidence: 99%
“…In this study, the total organic acids was measured directly in clear supernatant after centrifugation and filtration using spectrophotometer at 220 nm (Sokullu et al, 2010) and values were compared to uninoculated control samples. Specific organic acids were not determined at this stage of this study.…”
Section: Determination Of Total Organic Acidsmentioning
confidence: 99%
“…A variety of analytical methods are available for monitoring lactic acid levels in beverages, meat, milk, etc., such as colorimetry, spectrophotometry, titration, chromatography, and proton nuclear magnetic resonance spectroscopy [1][2][3][4][5][6]. However, sample preparations for these methods are tedious and time consuming, and some methods also require skilled personnel and the use of expensive equipment.…”
Section: Introductionmentioning
confidence: 99%
“…Chemometric techniques are being used more widely in order to enhance analytical performance of LIBS [18]. Recent works have shown that multivariate analysis such as partial least square (PLS) and artificial neural network (ANN) give promising results for quantitative analysis [19][20][21][22]. These advanced techniques reduce the complexity of spectra and enable valuable information.…”
Section: Introductionmentioning
confidence: 99%